Epic fails - Loh-Hagan, Virginia (Loh-Hagan, Virginia. Stranger than fiction., 2018)
Highlights a selection of epic fails including a lost winning lottery ticket, surgeons who performed the wrong operation, and a rock climber who threw his rope into a bee hive. Includes text-related activities and questions, a glossary, and color photographs.